Nanotechnological prospective for enhancing the antibacterial activity of mupirocin and cinnamon essential oil: a combination therapy - Aldhubiab, Bandar; Almuqbil, Rashed M.; Shehata, Tamer M.; Soliman, Wafaa E.; Elsewedy, Heba S. (Frontiers in Pharmacology, 2024)
The aim of current study was to develop a distinctive nanolipid formulation namely; nanostructured lipid carrier (NLC) that would deliver an antibacterial medication such as Mupirocin (MP). Additionally, cinnamon essential oil (CEO), which is reported to exhibit antibacterial activity, was utilized in the development process in an attempt to improve the influence of MP.Methods: As a consequence, different MP-NLC formulations were developed using Central Composite Design (CCD) approach. One optimized formula was selected and incorporated within pre-formulated gel matrix providing MP-NLC-gel formula for efficient topical application. MP-NLC-gel was assessed for its physical characters to check its suitability for topical application, and evaluated for its in vitro drug release over 6 hours. Further, it studied for its stability at different conditions; 25 ± 2°C and at 4 ± 3°C, for 6 months. Finally, the formulation was examined for its antibacterial performance against gram positive and negative bacteria.The developed topical NLC-gel formulation demonstrated pH 5.8, viscosity 14510 cP and spreadability 58.1 mm, which were seemed to be satisfactory properties for successful topical application. The drug was released successfully over 6 hours with 52.9 %. Additionally, it was stable in both storage conditions for 6 months since it displayed non-significant variations in its evaluated characters compared to fresh preparation. Ultimately, the developed gel formulation could inhibit growth of different bacterial strains, especially gram negative one.To sum up, these findings would demonstrate the efficiency of NLC prepared with CEO and incorporating MP to be a promising antibacterial lipid nanocarrier.